Epiphytic bromeliad communities in secondary and mature forest in a tropical premontane area - Cascante Marín, Alfredo (2006)
We analyzed the differences in species richness, community composition, population structure and within-tree location of epiphytic bromeliads in contiguous secondary and mature forests in a premontane area in Costa Rica. Diversity in the mature forest was highest, and the communities differed in their composition as well as in the recruitment rates of the dominant species. Guzmania monostachia and Catopsis nutans dominated the secondary forests, whereas Tillandsia fasciculata and T. tricolor were more abundant in the mature forest. The secondary forest species showed high rates of seedling recruitment while the opposite was found for the mature forest species. Species presence and abundance among and within habitats did not correlate with their physiological (i.e. CAM vs. C3 photosynthesis) or morphological attributes. The spatial distribution patterns were similar among habitats; bromeliads tended to aggregate on a few relatively large phorophytes. The species shared a similar vertical stratification within habitats, except for the two dominant species in the early and mid-successional stages, although its ecological implication is not clear. With some exceptions, conspecifics of different ages were located on similar substrate types (i.e. stems, primary, secondary, or tertiary branches) within the tree-crowns, which suggests limited within-tree dispersion. Differences in species composition and rates of seedling recruitment among secondary and mature forest may arise from ecophysiological differences among species; however, the combined effect of seed availability and dispersal differences may have a larger influence. Thus, epiphyte community assembly can only be understood when the differences in habitat conditions, the availability of propagules, their dispersal characteristics and requirements for seedling establishment are known.